Discipline of architecture - Piotrowski, Andrzej; Robinson, Julia Williams (London: Univ Of Minnesota Press, 2000)
Architecture A polemical look at how architectural knowledge is produced, disseminated, and received. In the vast literature on architectural theory and practice, the ways in which architectural knowledge is actually taught, debated, and understood are too often ignored. The essays collected in this groundbreaking volume address the current state of architecture as an academic and professional discipline. The issues considered range from the form and content of architectural education to the architect's social and environmental obligations and the emergence of a new generation of architects. Often critical of the current paradigm, these essays offer a provocative challenge to accepted assumptions about the production, dissemination, and reception of architectural knowledge. Contributors: Sherry Ahrentzen, U of Wisconsin-Milwaukee; Stanford Anderson, MIT; Carol Burns, Harvard U; Russell Ellis, UC Berkeley; Thomas Fisher, U of Minnesota; Linda Groat, U of Michigan; Kay Bea Jones, Ohio State U; David Leatherbarrow, U of Pennsylvania; A. G. Krishna Menon, TVB School of Habitat Studies, India; Garth Rockcastle, U of Minnesota; Michael Stanton, American U, Beirut; Sharon E. Sutton, U of Washington; David J. T. Vanderburgh, Universit Catholique de Louvain, Belgium; and Donald Watson, Rensselaer Polytechnic Institute. Andrzej Piotrowski is associate professor of architecture and Julia Williams Robinson is professor of architecture, both at the University of Minnesota. Translation Inquiries: University of Minnesota Press.
Keywords: Architectural design--Philosophy; Architecture--Study and teaching